Impact of elexacaftor/tezacaftor/ivacaftor on lung function, nutritional status, pulmonary exacerbation frequency and sweat chloride in people with cystic fibrosis: real-world evidence from the German CF RegistryResearch in context - Sivagurunathan Sutharsan; Stefanie Dillenhoefer; Matthias Welsner; Florian Stehling; Folke Brinkmann; Manuel Burkhart; Helmut Ellemunter; Anna-Maria Dittrich; Christina Smaczny; Olaf Eickmeier; Matthias Kappler; Carsten Schwarz; et al. (Elsevier, 2023)
Summary: Background: Treatment with elexacaftor/tezacaftor/ivacaftor (ETI) improves multiple clinical outcomes in people with cystic fibrosis (pwCF) with at least one F508del allele. This study evaluated the real-world impact of ETI on lung function, nutritional status, pulmonary exacerbation frequency, and sweat chloride concentrations in a large group of pwCF. Methods: This observational cohort study used data from the German CF Registry for pwCF who received ETI therapy and were followed up for a period of 12 months. Findings: The study included 2645 pwCF from 67 centres in Germany (mean age 28.0 ± 11.5 years). Over the first year after ETI was initiated, percent predicted forced expiratory volume in 1 s (ppFEV1) increased by 11.3% (95% confidence interval [CI] 10.8-11.8, p < 0.0001), body mass index (BMI) z-score increased by 0.3 (95% CI 0.3-0.4, p < 0.0001) in individuals aged 12 to <18 years and BMI in adults increased by 1.4 kg/m2 (95% CI 1.3-1.4, p < 0.0001), pulmonary exacerbations decreased by 75.9% (p < 0.0001) and mean sweat chloride concentration decreased by 50.9 mmol/L (95% CI -52.6, −49.3, p < 0.0001). Improvements in ppFEV1 over the first year of therapy were greater in pwCF who had not previously received cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapy (12.6% [95% CI 11.9-13.4] vs. 9.7% [95% CI 9.0-10.5] in those with prior CFTR modulator treatment. Interpretation: These real-world data are consistent with the findings of randomised clinical trials, and support the use of ETI as a highly effective treatment option for pwCF who have at least one F508del allele. Funding: None.